Density of mast cells and microvessels in minor salivary gland tumors - Vidal, Manuela Torres Andion (2013)
Federal University of Bahia. School of Dentistry. Laboratory of Surgical Pathology. Department of Oral Pathology. Salvador, BA, Brasil.